Immunological response of polysaccharide nanogel-incorporating PEG hydrogels in an in vivo diabetic model. Issue 14 (22nd September 2022) - Bal, Tugba; Karaoglu, Ismail Can; Murat, Fusun Sevval; Yalcin, Esra; Sasaki, Yoshihiro; Akiyoshi, Kazunari; Kizilel, Seda
Abstract: Cell-based therapies hold significant advantages in comparison with the traditional drug-based or injection-based treatments. However, for long-term functional cellular implants, immune acceptance must be established. To accomplish the acceptance of the implanted cells, various biomaterial systems have been studied. Nanogels have shown great potential for modulation of cellular microenvironments, acting as a physical barrier between the immune system and the implant. However, internalization of nano-scale materials by implanted cells is not desirable and is yet to be overcome. In this study, we incorporated acrylate modified cholesterol-bearing pullulan (CHPOA) nanogels into poly (ethylene glycol) diacrylate (PEGDA) hydrogels through covalent crosslinking, where we used visible light-induced photopolymerization. We characterized morphology and swelling properties of CHPOA incorporated PEG composite hydrogels using FE-SEM and gravimetric analysis. Also, we investigated the biocompatibility properties of composite hydrogels in vivo, where we used both healthy and diabetic mice. We induced diabetes in mice using a low dose streptozotocin (STZ) injections and implanted composite hydrogels in both diabetic and healthy mice through subcutaneous route. Immune cell infiltration of the retrieved tissue was examined through histological analysis, where we observed minimum immune response levels of 0–2 rareness, according to ISO standard of biological evaluation of medical devices. Our observation suggests that the composite hydrogel developed here can be used to introduce nanostructured domains into bulk hydrogels and that this system has potential to be used as immunologically acceptable composite material in cellular therapy without internalization of nanoparticles. Abstract : UF0001